(untitled) (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2021)
The acceptance of a diverse world begins with recognition at an early stage in life. However, not everyone steps out of their home with an empathic approach and this is why intercultural education should start as early as possible. The main objective of the study is to introduce the opportunities inherent in fairy tales from the perspective of intercultural education via the introduction of fairy tales dealing with multiple aspects of being different; and to introduce the practices applied in the Hungarian educational environment. The tales are analyzed with the method of content analysis, with special respect to diversity and cultural differences; then their educational applicability is analyzed based on the conclusions that can be drawn. The paper introduces the threats and opportunities of applying tales in intercultural education at a very young age, suggesting fairy tales to be used actively, but with suitable professionalism.